Low‐Coherence Interferometer with Nanocrystalline Diamond Films with Potential Application to Measure Small Biological Samples. Issue 22 (20th June 2018) - Hirsch, Marzena; Kosowska, Monika; Majchrowicz, Daria; Struk, Przemysław; Wierzba, Paweł; Ficek, Mateusz; Sankaran, Kamatchi J.; Haenen, Ken; Jędrzejewska‐Szczerska, Małgorzata
Abstract : The study investigates a case of a low‐coherence fiber‐optic Fabry–Pérot interferometer with a nanocrystalline diamond (NCD) mirror. The method of achieving double density of interference fringes is proposed by the application of birefringent material in the cavity of the interferometer. It can be used to reduce sample volume in comparison to conventional interferometers. The use of a biocompatible diamond mirror makes it specifically well suited for application in biosensing. The fabrication process and surface characterization of the nitrogen‐doped NCD and boron‐doped NCD films are described. The results of numerical modeling and experimental measurements are discussed. Abstract : The application of boron‐doped diamond and nitrogen‐doped diamond films as a mirror in a fiber‐optic Fabry–Pérot interferometer is presented. This enables performing biomedical measurements. The birefringent material is introduced into sensor cavity which allows us to reduce the sample volume for measurements. This could be useful in case of biological samples.